Statistical Feature Analysis for Ulcer and Bleeding Detection in Capsule Endoscopy Images - SUMAN, SHIPRA (2018)
Visual quality of a color image plays a significant role in the diagnosis of the endoscopic images. The images obtained from a capsule are of lower quality, however higher quality images are required by gastroenterologist to make an accurate diagnosis.